A study on the technology of enhancing gas permeability and gas drainage by sectional hydraulic fracturing in directional long boreholes: a case study of the no. 8 coal seam in baode coal mine - Zenghui Zhang; Jinlin Qiao; Sen Yang; Kaige Zheng; Di Zhang; Jian Zhang (Frontiers in Earth Science)
Aiming at the technical problem of low efficiency of gas drainage in high-gas and low-permeability coal seams in China, this paper takes the No. 8 coal seam in Baode Coal Mine as the engineering background and conducts a study on the technology of enhancing gas permeability and gas drainage through staged hydraulic fracturing of directional long boreholes. By adopting the drag-type staged fracturing process with double-packers and a single-slip, and combining it with methods such as the analysis of pump injection stress curve stages, gas extraction concentration analysis, and in-hole transient electromagnetic detection, the laws of fracture propagation and the mechanism of permeability modification are revealed. The research shows that during the rock formation fracturing stage, the stress drop reaches 8.2–9.6 MPa, and the drop rate of the fracturing stress from the bottom to the opening of the borehole is approximately 14.6%. The influence radius of the fracturing extends to 30 m, forming a strip-shaped low-resistance abnormal area. The gas extraction data indicates that after fracturing, the gas extraction concentration increases to 54.37% (with a peak value of 68%), the comprehensive flow rate increases by 200%–300% (stabilizing at 0.6–0.8 m3/min), which is 5.6 times higher than that of the unfractured boreholes. Through reconstructing the fracture network of the coal seam, this technology can break through the limitations of the original gas permeability, shorten the pre-extraction cycle, and reduce the borehole density. The research results provide theoretical support and engineering demonstration for the efficient gas extraction from coal seams with similar geological conditions.